EXPLORING THE LINK BETWEEN WATER CHEMISTRY VARIATION AND FISH DIVERSITY IN RIVER JHELUM: A META-ANALYSIS - GUL, SHAHID; PRAKASH, SWADESH; QURESHI, NEHA W.; YADAV, BINOD KUMAR; SHARMA, ARPITA; MIR, SHAKIR AHMAD (Journal of the Inland Fisheries Society of India, 2025)
This study aimed to establish a connection between changes in the water chemistry of the river Jhelum and the diversity, richness, and abundance of species over time. Empirical evidence was reviewed from existing literature on fish species diversity and physicochemical parameters. A comparison was made between the upper and lower sections of the river, considering both spatial and temporal aspects. The dominant fish family in the river was Cyprinidae, consisting of eight species, followed by Nemachilidae, with only two species. Regarding diversity indices, the upper stretch exhibited values of 2.192 for the Shannon-Wiener diversity index (H’), 0.104 for Simpson’s dominance index (D), 0.896 for the heterogeneity index (1-D), 1.436 for Margalef’s index (d), and 0.350 for Pielou’s evenness index (J’). Conversely, the lower stretch showed values of 1.978, 0.145, 0.855, 1.144, and 0.323, respectively. These findings indicated a decline in fish species diversity, richness, and relative abundance in the lower section. These results align with existing literature, suggesting that water pollution is more severe in the lower stretch compared to the upper stretch. However, correlation analysis revealed that, except for dissolved oxygen and ortho phosphorous, there is a negative relationship between water quality parameters and fish diversity, which, while present, is not significant enough to impact the river’s fish diversity substantially. This suggests that other anthropogenic activities, such as sand mining, overfishing, and exotic common carp in the river, are responsible for the decreased fish diversity downstream in the river Jhelum. Further research is needed to investigate the effects of other hydrological parameters, such as precipitation, evapotranspiration, surface runoff, water velocity, and depth, on the fish diversity of the river Jhelum. Such studies would provide additional empirical evidence for protecting the aquatic fish biodiversity in the river Jhelum.